Integrating Green Finance and Environmental Practices to Enhance SMEs' Business and Sustainable Performance - Budisaptorini, Anasthasia Triwulan; Wibowo, Andri (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study explores the integration of green finance and green environmental practices and their impact on the business and sustainable performance of SMEs, specifically among tempeh entrepreneurs in Sanan, Malang. A quantitative research design was adopted to rigorously analyze these relationships. The population comprised 145 tempeh entrepreneurs, from which a representative sample of 106 respondents was selected using Slovin's formula, ensuring a margin of error that balances precision and feasibility. Data collection was conducted through structured questionnaires that captured the extent of green finance implementation, the adoption of green environmental practices, and their perceived impact on business and sustainable performance. The collected data were then analyzed using Partial Least Squares (PLS), a robust statistical technique that allows for the modeling of complex relationships among the variables. The analysis confirmed that both green finance and green environmental practices significantly and positively influence the business performance and sustainability of SMEs. These findings underscore the critical role of environmentally conscious financial and operational strategies in driving sustainable growth within the SME sector. By integrating these practices, tempeh entrepreneurs can not only enhance their business performance but also contribute to broader environmental sustainability.